2022
DOI: 10.3390/nu14010204
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Birth Weight and Metabolic Syndrome in Children

Abstract: Small and large birth weights (BWs) for gestational age (GA) represent extremes, but the correlation between extreme BW and metabolic syndrome (MetS) has not been fully elucidated. In this study, we examined this correlation in obese children based on changes in their metabolic profile from childhood to adolescence. A retrospective observational study was performed on 535 obese patients aged 0–18 years in the Clinical and Emergency Hospital for Children “Louis Turcanu” in Timisoara, Romania, based on clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
1
8
0
1
Order By: Relevance
“…We found that SGA was associated with increased risk for hypertensive BP in children with overweight or obesity, both in children born preterm and full-term. In line with our finding, 2 hospital-based studies in Germany and Romania of children with overweight found a higher prevalence of hypertension in children born SGA, but the studies included only children born full-term [ 16 , 18 ]. In contrast, results in the general population showed different directions, partly depending on the age when BP was measured.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found that SGA was associated with increased risk for hypertensive BP in children with overweight or obesity, both in children born preterm and full-term. In line with our finding, 2 hospital-based studies in Germany and Romania of children with overweight found a higher prevalence of hypertension in children born SGA, but the studies included only children born full-term [ 16 , 18 ]. In contrast, results in the general population showed different directions, partly depending on the age when BP was measured.…”
Section: Discussionsupporting
confidence: 88%
“…Childhood obesity is per se a risk factor for cardiometabolic diseases [15] and to which extent perinatal factors contribute to the risk for cardiometabolic comorbidities in children with obesity remains unclear. Evidence in children with overweight/obesity is scarce and inconsistent [16][17][18][19]. For example, one study found an association between SGA and hypertension [16], while the other study reported no association [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existen diversos estudios que relacionan el PBN y desarrollo de SM en la infancia [15][16][17] . La identificación temprana de individuos con factores de riesgo, incluido el PBN para el desarrollo de SM, permitirá realizar intervenciones precoces para la prevención de una rápida ganancia de peso durante la infancia.…”
Section: Introductionunclassified
“…Children born large for gestational age predominated over those born small for gestational age. Birth weight had an independent effect on triglycerides and insulin resistance (two well-known biomarkers of cardiometabolic risk) during childhood, whereas obesity had a direct influence on hypertension, an impaired glucose metabolism, and hypertriglyceridemia [ 1 ].…”
mentioning
confidence: 99%